2016
DOI: 10.7456/1060agse/082
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Organizational Culture and Knowledge Management Components of Lawson

Abstract: This study aimed to investigate the relationship between organizational culture and its relation with knowledge management. This is a correlational study and its statistical population consisted of all nurses working in hospitals of Zahedan Medical Sciences University. The sample size by using Morgan table was 250 persons that were selected by stratified random sampling method in proportion to population size within classes. The instrument used in this study was a questionnaire containing 60 questions of Denis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…(2004) stated that knowledge acquisition is an activity that refers to accessing and absorbing knowledge from its sources. Knowledge application expresses the use or reuse of knowledge in new situations (Lawson, 2003; del Rosario Pérez-Salazar, 2017), while knowledge capitalization is an activity that indicates the protection, accumulation, storage and retrieval of knowledge to access it effectively and easily (Lawson, 2003; Lehyani and Zouari, 2015b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2004) stated that knowledge acquisition is an activity that refers to accessing and absorbing knowledge from its sources. Knowledge application expresses the use or reuse of knowledge in new situations (Lawson, 2003; del Rosario Pérez-Salazar, 2017), while knowledge capitalization is an activity that indicates the protection, accumulation, storage and retrieval of knowledge to access it effectively and easily (Lawson, 2003; Lehyani and Zouari, 2015b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Culture is influential in knowledge-related behaviors of individuals, teams, organizational units and overall organizations, because it determines which knowledge is appropriate to share, with whom, and when. So, it is essential to create a culture in which access to knowledge is easy, this is particularly the case for managers during the implementation of KM (Mojibi et al, 2015;Sanavi et al, 2016).…”
Section: Technology For Knowledge Sharing (Tks)mentioning
confidence: 99%
“…Culture may also act as a barrier to knowledge sharing and the success of KM (Chang et al, 2017;Sanavi et al, 2016). Organizational culture is influenced by the mindset and individual culture established at each level of the organization and becomes a challenge to encourage efficiency.…”
Section: Technology For Knowledge Sharing (Tks)mentioning
confidence: 99%
See 1 more Smart Citation
“…(Denison et al, 2014) Sackmann (2011 Have identified 45 studies of organizational culture between 2000 and 2009, showing that the concept remains valid. For the purposes of this study, organizational culture is understood as the combination of values, beliefs, symbols and models of behavior that regulate workers' behavior (Sanavi, Robati, & Sanavi, 2016).…”
Section: Organizational Culturementioning
confidence: 99%